A Longitudinal Study of the Evolution of Neuropsychological Change in Amyotrophic Lateral Sclerosis: The Incidence, Nature and Progression of Language Impairment. - PINTO-GRAU, MARTA (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
Background: Amyotrophic Lateral Sclerosis is a multi-system disease that also affects cognition and behaviour. Cognitive change in ALS manifests most commonly as executive dysfunction. Although changes in language function have been described, these have not been investigated within a large population-based sample of incident cases. Objective: To investigate the existence of different neuropsychological phenotypes within the ALS disease spectrum, with a special focus on language function. Method: A large incident population-based ALS sample was recruited. An observational, prospective, case-control design was employed, with complementary cross-sectional and longitudinal analyses. Results: The population-based incidence of ALS frontotemporal syndromes in our sample was as follows: 9% presented with single cognitive impairment, 18% with single behavioural impairment, 15% with both cognitive and behavioural impairment, 13% with comorbid FTD, and 33% with preserved cognitive function and behaviour. Incident language deficits were confined to the domains of word retrieval, orthographic lexical processing and syntactic/grammatical processing. Phonological lexical processing as well as semantic processing were spared at early stages in ALS. Language change was associated with executive dysfunction to a degree, although pure deficits of linguistic nature were observed. A more aggressive disease phenotype was identified, which was characterised by more generalised cognitive presentations including executive dysfunction and language impairment along with behavioural change, as well as by a more rapid progression of motor symptoms and shorter survival. In contrast, a more pure motor phenotype characterised by slower functional decline and no behavioural or cognitive deficits was also observed. The C9orf72 hexanucleotide repeat expansion was related to a more extensive propagation of ALS pathology also affecting cognition and behaviour, whereas sporadic ALS patients more frequently presented with less aggressive forms of disease. Conclusions: These findings support the current conceptualization that the neuropsychological profile in ALS falls along a spectrum of frontotemporal involvement, with distinct disease phenotypes representing varying patterns of disease spread. Neuropsychological status in ALS is therefore an important disease marker with significant implications for disease management and prognosis.
APPROVED
Keywords: Amyotrophic Lateral Sclerosis (ALS); Neuropsychology; ALS - Frontotemporal Spectrum Disorder (ALS-FTSD); Language